Awareness, service use and barriers to sexual and reproductive health among adolescents in the Arsi Zone, Oromia, Ethiopia - Derese T. Demissie; Rose Mmusi-Phetoe (African Journal of Primary Health Care & Family Medicine, 2026)
Background: Sexual and reproductive health (SRH) services are crucial for adolescents, yet utilisation remains low in the Arsi Zone of Ethiopia. Identifying the factors affecting adolescents’ use of SRH services is important to address the problem. Aim: To explore and describe adolescents’ awareness and barriers to SRH services in Arsi Zone, Ethiopia, and improve SRH service use, ultimately reducing preventable SRH-related illness and death among adolescents. Setting: The study was conducted at six districts of Arsi Zone, Oromia, Ethiopia. Methods: A school-based cross-sectional study was conducted among 651 randomly selected adolescents aged 15–19 years in Arsi Zone of Ethiopia, from 01 January 2024 to 29 February 2024. Data were collected using a self-administered structured questionnaire. A multivariable logistic regression model was employed to analyse the data. Measures of association were expressed as adjusted odds ratios (AORs) with corresponding 95% confidence intervals (CIs). Results: This study revealed that being involved in SRH discussions with trusted individuals was significantly associated with SRH utilisation, with better odds (AOR = 2.12; 95% CI: 1.22–3.67). Absence of fear when seeking care was significantly associated with higher utilisation of SRH services (AOR = 2.07; 95% CI: 1.12–3.83). The presence of an SRH problem, such as a sexually transmitted infection (STI), was strongly associated with SRH service utilisation (AOR = 4.88; 95% CI: 2.26–10.54). In addition, the perceived convenience of service operating hours was significantly associated with higher SRH service utilisation (AOR = 3.19; 95% CI: 1.57–6.52). Conclusion: The findings highlight a significant gap between awareness and use of SRH services among adolescents. This emphasises the need for targeted interventions to improve awareness and access to SRH services for adolescents. Contribution: The study provides empirical evidence on Ethiopian adolescents’ SRH, addressing gaps in service access, structural and sociocultural barriers, and service use. Its findings offer actionable insights for designing, implementing and evaluating adolescent SRH policies and programmes and contribute to the academic literature.